THE IMAGE OF THE MOTHER IN LITERATURE (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the image of the mother in literature, examining its development and diversity through various eras and cultural contexts. Starting with ancient myths and tragedies, it traces the evolution of this image in medieval religious literature, Renaissance and Enlightenment works, as well as in 19th and 20th-century literature. Special attention is given to modern interpretations and psychological aspects of motherhood. Analyzing the works of authors such as Leo Tolstoy, Fyodor Dostoevsky, William Shakespeare, Franz Kafka, Maxim Gorky, Toni Morrison, and Haruki Murakami, the article reveals the role of the mother as a symbol of love, sacrifice, resilience, and spiritual wisdom. The presented material underscores the relevance of the mother's image in literature and its impact on readers.